Assessing phytolith preservation in a Late Quaternary loess-paleosol sequence from the Kashmir Valley, Northwest Himalaya, India - Waseem Qader; Reyaz Ahmad Dar; Ishfaq Ul Rehman; Irfan Rashid; Suhail Hussain Sheikh (Quaternary Science Advances)
Phytolith content and its preservation in soils form a robust tool for paleoecological reconstruction. Post-depositional processes, however, influence the preservation of phytolith assemblages in soils thus making the paleoecological inferences biased. Here we evaluated the preservation of phytoliths in a Late Quaternary loess-paleosol sequence (LPS) from Kashmir Valley, northwest Himalaya. The soil micromorphological study, physicochemical parameters, phytolith morphometry, and phytolith translocation rates were employed to assess phytolith preservation and absence (not recorded) in the various litho-units of the Wanihama LPS. The comparison of phytolith content and soil physio-chemical parameters including pH, electrical conductivity, available N, P, K, organic carbon, extractable Fe, Zn, Mn and Cu do not show any significant correlation. This suggests that soil physicochemical parameters have a minor role in regulating the preservation of phytoliths in the LPS. The depth distribution of phytoliths exhibits an inconsistent pattern and phytolith content doesn't decrease systematically with depth. The phytolith content usually follows the loess-paleosol stratigraphy, with low concentrations in loess units and high concentrations in paleosols indicating that phytolith assemblages in the LPS have not been altered or translocated as a result of pedogenic processes. The micromorphological observations suggest weak pedogenesis and the sequence does not seem to be significantly mixed by bioturbation activities. This is augmented by the low translocation rate of <18%, and phytolith morphometry suggesting well-preserved phytoliths with minimum morphological alterations along the depth. The absence of phytoliths at certain stratigraphic units in the LPS thus suggests that climatic conditions rather than physicochemical parameters determine the phytolith preservation and their content in the Kashmir LPS.